Impact of Forest Canopy Closure on Snow Processes in the Changbai Mountains, Northeast China - Gao, Yuan; Shen, Lidu; Cai, Rongrong; Wang, Anzhi; Yuan, Fenghui; Wu, Jiabing; Guan, Dexin; Yao, Huaxia (Frontiers in Environmental Science, 2022)
Forest canopy closure affects snow processes by changing the redistribution of snowfall, snow interception, accumulation, sublimation, and melt. However, how the mixed forest closure impacts the snow processes of different period has not been explored. To address this issue, we conducted 3-years snow density and depth and carried out snow process calculations (i.e., interception, sublimation, and snowmelt) from 2018 to 2021 in four mixed forests with different canopy closures and an open site in Changbai Mountain, Northeast China. We found that the snow density of the five study sites varied greatly (0.14-0.45 g/cm3). The snow depth (SD) at the four mixed forests sites was smaller than that of the nearby open site. The SD in the forests decreased as the forest canopy closure increased. Additionally, the forest interception effect increased with the canopy closure and decreased as the snowfall intensity increased. The total interception efficiency of the four mixed forests in normal snow years changed from 34% to 73% and increased with forest canopy closure. The averaged sublimation rate (Ss) and snowmelt rate (Sr) of the four mixed forests varied during different periods. The Ss was 0.1-0.4 mm/day during the accumulation period and 0.2-1.0 mm/day during the ablation period, and the Sr was 1.5-10.5 mm/day during the ablation period for the four studied forests. There was a good correlation between Ss, Sr, and canopy closure, but interannual variation was observed in the correlation. The four mixed forests affected the snow SWE (snow water equivalent) from -27% to -52% in normal snow years, and enhanced it in extreme low snow years. Moreover, the impact effect was correlated with the forest canopy closure and enhanced with the canopy closure. This study may provide more scientific support for future studies on snow cover response to forest management.